Effectiveness of Information–Motivation–Behavioral (IMB) Skills Model on Diabetes Mellitus Patients Knowledge - Exodus Maruaba Barutu; Dudut Tanjung; Nur Asnah Sitohang (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus (DM) is characterized by increased blood glucose levels caused by insulin deficiency or insulin resistance. Knowledge of diabetes mellitus plays an important role in reducing diabetes-related complications and improving its prevention.Knowledge about diabetes influences decision-making related to physical activity, diet, medication use, and health monitoring, including diabetes assessment and foot care. Model Information-Motivation-Behavioral Skills (IMB) is effective in being implemented in providing health education to patients.The purpose of the research is toanalyzing the effectiveness of the information–motivation–behavioral (IMB) skills model on the knowledge of diabetes mellitus patients. The research design was quasi-experimental nonequivalent control group design. The sampling technique was purposive sampling. The number of samples was 66 respondents. The instruments used are DKQ-24 (Diabetes Knowledge Questionnaire). Data analysis used dependent t-test and independent t-test. The results of data analysis showed the influence of the IMB skills model on pre- and post-test knowledge in the intervention and control groups with a p value = 0.000 (<0.05). The results of statistical tests also showed that there was a difference in the influence of the intervention between the intervention and control groups with a p value = 0.000 (<0.005). This study proves that the IMB skills model is effective in improving the knowledge of diabetes mellitus patients.